2015
DOI: 10.3390/f6124377
|View full text |Cite
|
Sign up to set email alerts
|

Applying Resilience Concepts in Forest Management: A Retrospective Simulation Approach

Abstract: Abstract:Increasing the resilience of ecological and sociological systems has been proposed as an option to adapt to changing future climatic conditions. However, few studies test the applicability of those strategies to forest management. This paper uses a real forest health incident to assess the ability of forest management strategies to affect ecological and economic resilience of the forest. Two landscape scale strategies are compared to business as usual management for their ability to increase resilienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…It has also been found that diversifying the forest in combination with harvesting the most dominant or high‐risk tree species may lead to greater ecological resilience, higher harvest rates, and higher net revenue over time than business‐as‐usual strategies (Dymond et al. , ). However, those studies also demonstrated that it may not be possible to increase the diversity of some forests through planting alone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has also been found that diversifying the forest in combination with harvesting the most dominant or high‐risk tree species may lead to greater ecological resilience, higher harvest rates, and higher net revenue over time than business‐as‐usual strategies (Dymond et al. , ). However, those studies also demonstrated that it may not be possible to increase the diversity of some forests through planting alone.…”
Section: Discussionmentioning
confidence: 99%
“…A study of forest management adaptation options in Austria, while more comprehensive than ours, found options like promoting mixed stands of species adapted to changing climatic conditions, forestry techniques encouraging complexity, and increased intensity of forest management were available to move away from current management and reduce vulnerability in timber supply, carbon stocks, and productivity although not necessarily to zero vulnerability (Seidl et al 2011). It has also been found that diversifying the forest in combination with harvesting the most dominant or highrisk tree species may lead to greater ecological resilience, higher harvest rates, and higher net revenue over time than business-as-usual strategies (Dymond et al 2014(Dymond et al , 2015b. However, those studies also demonstrated that it may not be possible to increase the diversity of some forests through planting alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The resilience of the system is its ability to absorb a shock wave in such a way that it can return to a normal state with the least possible delay and with the least possible dysfunction (IPPC 2012;Dymond et al 2015). Ensuring decisionmakers have a high level of information and preparedness corresponds with the enhancement of this systemic resilience.…”
Section: Risk Mitigation At the Systemic Levelmentioning
confidence: 99%